Dietary Diversity and Nutritional Status of the Oraon Tribal Women: An Anthropometric Measurement Approach - Kujur, Seema; Barua, Sukanya; Nain, Manjeet Singh; Sahu, Subhashree; Sangeetha, V; Praveen, K V; Jha, Girish Kumar; Nath, Rajat Kumar; Gudla, Manichandana (Indian Journal of Extension Education, 2025)
The study was conducted among the Oraon tribal women of Chhota Nagpur Plateau, comprising Jharkhand and Chhattisgarh, during 2024-25. Using multi-stage random sampling, 400 respondents were selected. The data concerning dietary diversity was collected using a structured interview schedule. Anthropometric measurement tools, including BMI and MUAC, were employed to measure nutritional status. Only 22 per cent of the respondents met the minimum dietary diversity criteria, and 78 per cent of women had an inadequate nutritional intake, eating less than five defined food groups. A Welch’s ANOVA test highlighted significant variation in dietary intake across selected districts. Only 37.75 per cent of the women had normal BMI, whereas 48.75 per cent were affected by chronic energy deficiency, and a transition towards obesity was evident. 73.50 per cent of women were in the undernutrition category, defined by a MUAC cut-off below 22.8 cm. A comparison of nutritional status across selected districts highlighted no significant difference. The Pearson correlation analysis indicated a significant positive relationship between BMI and MUAC. The findings highlighted the efforts to address malnutrition in Oraon tribal women and enhance women’s nutritional outcomes through kitchen gardening, nutrition sensitive agriculture, and effective implementation of government nutrition programs.
Keywords: Oraon tribal women; Nutritional status; Dietary diversity; Anthropometry; Body mass index; Undernutrition; Malnutrition